Batas Akhir Waktu Salat dan Waktu Terlarang: Integrasi Fikih dan Sains - Katili, Moh Tantawi; Katili, Syarifuddin (UIN ALAUDDIN MAKASSAR, 2024)
This article aims to compromise the two well-known hadiths of Imāmah Jibrīl and ʻAbdullāh bin ʻAmr, which are apparently contradictive each other, and explain further about forbidden times. It employs a literature study, with a post-positivistic/naturalistic approach. The collected data was analyzed using content analysis. The result shows that the two hadiths can harmonize by dividing the time into several types, allowing each prayer to end when the next one begins, except for Fajr. Astronomically, variations in shadow length at the end of Zuhur result from the value |ϕ-δ☼|, while the sun’s elevation for the end of Asr and Fajr or the end of Maghrib and Isha is relatively similar. The forbidden times are divided into: 1) from after the Fajr prayer until the sun rises at least 3°30', 2) from local noon time (12–EoT–Interpolation) until declining-sun, and 3) from after the Asr prayer until sunset.